2017
DOI: 10.1103/physrevd.96.086020
|View full text |Cite
|
Sign up to set email alerts
|

Dyon degeneracies from Mathieu moonshine symmetry

Abstract: We construct the Siegel modular forms associated with the theta lift of twisted elliptic genera of K3 orbifolded with g corresponding to the conjugacy classes of the Mathieu group M 24 . We complete the construction for all the classes which belong to M 23 ⊂ M 24 and two other classes outside the subgroup M 23 . For this purpose we provide the explicit expressions for all the twisted elliptic genera in all the sectors of these classes. We show that the Siegel modular forms satisfy the required properties for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 51 publications
(225 reference statements)
0
40
0
Order By: Relevance
“…the McKay-Thompson series. This was studied explicitly for the compactifications of the heterotic E 8 × E 8 string theory on K3 × T 2 in [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…the McKay-Thompson series. This was studied explicitly for the compactifications of the heterotic E 8 × E 8 string theory on K3 × T 2 in [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…We adapt the proof of [10] for configurations with magnetic charge P 2 = 2 and demonstrate that the index is positive. We then extend this observation to all the CHL models and to other orbifolds associated with Mathieu moonshine introduced in [11,12].…”
Section: Jhep03(2021)106mentioning
confidence: 72%
“…In [11,13] it was observed that for N = 4 models obtained by freely acting Z 2 , Z 3 orbifolds of type IIB on T 6 , the index for single centered configurations after factorising…”
Section: Jhep03(2021)106mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was shown in [30] that the Gromov-Witten invariants of certain CY 3 manifolds are connected to Mathieu moonshine. This was further explored and studied in [31][32][33][34][35].…”
Section: Jhep02(2018)129mentioning
confidence: 99%